Secondary Prevention Medications Post Coronary Artery Bypass Grafting Surgery—A Literature Review. (July 2021) - Dimitriadis, Stavros; Qian, Evelyn; Irvine, Amy; Harky, Amer
Secondary prevention after coronary artery bypass graft (CABG) surgery is imperative in slowing the progression of atherosclerosis in both native and grafted vessels. Aspirin and statins remain the key medications for all patients without significant contraindications. The evidence for dual antiplatelet therapy with clopidogrel is less convincing, but there is hope for newer antiplatelet agents, such as ticagrelor. Meanwhile, β-blockers and angiotensin converting enzyme inhibitors might only offer benefits to specific sub-groups. Post-CABG patients appear to have different medication needs to the general cardiovascular patient and respond differently. In this review, we cover the drug regimens proposed by recent guidelines and the evidence behind their use. Assessing the evidence behind these recommendations, we find that there is an unmet need in some areas for robust population-specific evidence. We hope that future research will address this gap.